2003
DOI: 10.1023/b:jarg.0000006706.21588.0d
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Production of Nitric Oxide and Its Role in Implantation: A Pilot Study

Abstract: Purpose : To investigate the ability of human embryos to produce nitric oxide (NO) and correlate its production with embryo quality and pregnancy rate. Methods : Twenty-three women participated in the study and were submitted to controlled ovarian stimulation and intracytoplasmic sperm injection. Embryos were singularly cultured in medium microdrops of 50 µL and were replaced, by transcervical transfer, at the 2-to 6-cell stage. In the culture media of each embryo the NO production was assessed by monitoring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…Battaglia et al were the first to demonstrate secretion of NOx in human preimplantation embryos. They showed that embryonic mean NOx concentrations were significantly higher in embryos transferred that resulted in pregnancy when compared to nonpregnant patients, p=0.02 (18). This study differs from ours in that all embryos in the former were transferred at the 2-4 cell stage, hence limiting the ability to comment on sequential morphology or blastocyst progression over time.…”
contrasting
confidence: 69%
“…Battaglia et al were the first to demonstrate secretion of NOx in human preimplantation embryos. They showed that embryonic mean NOx concentrations were significantly higher in embryos transferred that resulted in pregnancy when compared to nonpregnant patients, p=0.02 (18). This study differs from ours in that all embryos in the former were transferred at the 2-4 cell stage, hence limiting the ability to comment on sequential morphology or blastocyst progression over time.…”
contrasting
confidence: 69%
“…In fact, although Chwalisz et al [17] demonstrated that NO is required for normal embryonic development, Barroso and co-workers [18] showed that high NO concentrations, in mice, may be cytotoxic and could alter the embryo development in vitro, and its implantation in vivo. Similar results were obtained in humans [15,16].…”
Section: Introductionsupporting
confidence: 89%
“…Although the precise role of NO has not been elucidated, it has been suggested that NO participates in periovulatory modulation of ovarian blood flow and seems to be involved in follicular maturation and ovulation [10,12,13]. A critical level of NO seems to be mandatory for the establishment of pregnancy [14][15][16]. In fact, although Chwalisz et al [17] demonstrated that NO is required for normal embryonic development, Barroso and co-workers [18] showed that high NO concentrations, in mice, may be cytotoxic and could alter the embryo development in vitro, and its implantation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals it is a potent vasodilator with short half-life, and an important cell signaling molecule that is involved in many physiological and pathological processes (Hou, 1999). It has been reported that localized NO synthesis in reproductive tissue plays an important role in regulating certain reproductive functions such as endometrial, cervical and myometrial activity (Telfer, 1995), embryo implantation (Battaglia, 2003) as well as embryo development (Chwalisz, 1999). While it is apparent from these studies that NO plays key roles in early pregnancy and even parturition, its concentration must be tightly regulated as it has also been reported that aberrant NO levels have been associated with embryo cytotoxicity (Barroso, 1999), early embryo loss (Haddad, 1995), as well as preterm labor (Cella, 2010).…”
Section: The Progesterone Receptor -To Be or Not To Be: The Anti-inflmentioning
confidence: 99%